Heterotopic Pregnancy- Case Report - Jahan, S; Das, TR; Akter, L (Journal of Bangladesh College of Physicians and Surgeons, 2011)
DOI: 10.3329/jbsp.v29i1.7171 J Bangladesh Coll Phys Surg 2011; 29:44-45